2011
DOI: 10.1002/tox.20752
|View full text |Cite
|
Sign up to set email alerts
|

Gallic acid provokes DNA damage and suppresses DNA repair gene expression in human prostate cancer PC‐3 cells

Abstract: Our earlier studies have demonstrated that gallic acid (GA) induced cytotoxic effects including induction of apoptosis and DNA damage and inhibited the cell migration and invasion in human cancer cells. However, GA-affected DNA damage and repair gene expressions in human prostate cancer cells are still unclear. In this study, we investigated whether or not GA induces DNA damage and inhibits DNA repair gene expression in a human prostate cancer cell line (PC-3). The results from flow cytometric assay indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Though our present studies demonstrated that gallic acid had the possible cardiovascular protective roles from inhibiting platelet activation and its interaction with leukocytes, notably, gallic acid has been shown to induce apoptosis in tumor cells with higher sensitivity than that of normal cells in the comparative concentrations [7, 42, 43]. In fact, some of the concentrations of gallic acid used in our in vitro experiments are higher than those detected in plasma after acute intake of 50 mg gallic acid (as pure compound) or one cup of Assam black tea, which were within a low micromolar range (~4  μ mol/L) [5].…”
Section: Discussionmentioning
confidence: 94%
“…Though our present studies demonstrated that gallic acid had the possible cardiovascular protective roles from inhibiting platelet activation and its interaction with leukocytes, notably, gallic acid has been shown to induce apoptosis in tumor cells with higher sensitivity than that of normal cells in the comparative concentrations [7, 42, 43]. In fact, some of the concentrations of gallic acid used in our in vitro experiments are higher than those detected in plasma after acute intake of 50 mg gallic acid (as pure compound) or one cup of Assam black tea, which were within a low micromolar range (~4  μ mol/L) [5].…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, exposure to gallic acid (25 and 50 μM) suppressed the invasion and migration of PC-3 prostate cancer cells through down-regulation of MMP-2 and MMP-9 [154]. In another study, gallic acid (50, 100, and 200 μM) in PC-3 prostate cancer cells provoked DNA damage and inhibited expression of DNA repair genes, which contributed to gallic-induced growth inhibition [155]. Treatment with gallic acid (10–40 μg/mL) decreased cell viability, proliferation, invasion and angiogenesis HeLa and HTB-35 cervical cancer cells, but showed less cytotoxicity on normal cells (HUVEC), indicating a potential role of the compound in cervical cancer treatment [156].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…GA can also be isolated from the roots of Radix Paeoniae (white-flowered peony), which is commonly used to treat vascular and liver diseases in traditional Chinese medicine (Ho and Hong, 2011). It has been reported that GA possesses anti-oxidant (Kim, 2007), anti-inflammatory (Kroes et al, 1992) and anti-viral (Kreis et al, 1990) properties, and a well-documented anti-cancer activity (Yang et al, 2000; Liu et al, 2011; Ho et al, 2013). Recently, GA has been reported to act as a potent anti-oxidant and free radical scavenger in a rat PD model (Sameri et al, 2011).…”
Section: Introductionmentioning
confidence: 99%